2021
DOI: 10.1136/bmjopen-2020-044177
|View full text |Cite
|
Sign up to set email alerts
|

Test accuracy of faecal calprotectin for inflammatory bowel disease in UK primary care: a retrospective cohort study of the THIN data

Abstract: ObjectiveTo estimate the test accuracy of faecal calprotectin (FC) for inflammatory bowel disease (IBD) in the primary care setting using routine electronic health records.DesignRetrospective cohort test accuracy study.SettingUK primary care.Participants5970 patients (≥18 years) without a previous IBD diagnosis and with a first FC test between 1 January 2006 and 31 December 2016. We excluded multiple tests and tests without numeric results in units of µg/g.InterventionFC testing for the diagnosis of IBD. Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
2
10
2
1
Order By: Relevance
“…FC testing has a high negative predictive value of 99.6% (95% CI = 99.3% to 99.7%) at this threshold (and a positive predictive value of 8.1%, 95% CI = 7.1% to 9.2%). 26 Nevertheless, the present study showed that nearly 50% of patients with an FC level <50 µg/g were referred into secondary care services. This is in agreement with reported estimates from several primary care studies.…”
Section: Discussioncontrasting
confidence: 55%
“…FC testing has a high negative predictive value of 99.6% (95% CI = 99.3% to 99.7%) at this threshold (and a positive predictive value of 8.1%, 95% CI = 7.1% to 9.2%). 26 Nevertheless, the present study showed that nearly 50% of patients with an FC level <50 µg/g were referred into secondary care services. This is in agreement with reported estimates from several primary care studies.…”
Section: Discussioncontrasting
confidence: 55%
“… 26 Routinely collected data have also been used to evaluate the test accuracy of faecal calprotectin at different thresholds in the diagnosis of inflammatory bowel disease. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In this comparison, the tailored results were compared to the ‘true’ estimates for primary care from an independent study of routine primary care data [ 8 ]. That study may or may not be biased.…”
Section: Discussionmentioning
confidence: 99%
“…That study may or may not be biased. However, considering all strengths and limitations discussed previously [ 8 ], it probably represents the best estimate we are likely to achieve on the test performance of faecal calprotectin as it is used in UK primary care without conducting a de novo cross sectional study under tightly controlled study conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation